The Effect of Tax Avoidance and Tax Risk on Corporate Risk - Amrie Firmansyah; Rizka Muliana (University of Merdeka Malang, 2018)
Tax avoidance could increase the corporate risk for several reasons. First, tax avoidance increases the uncertainty of future corporate tax payments, second, the tax avoidance rate could serve as a leading indicator of the company's investment risk. We examined tax avoidance and tax risk on corporate risk. Corporate risk is uncertainty about the future net cash flows of the company as well as a type of risk inherent in management's decision-making arrangements. The sample used in this study were non-financial companies listed on the Indonesia Stock Exchange (IDX). The study used the method of purposive sampling; selected corporate data amounted to 80 so that the sample in this study amounted to 240 firm-years. The method examination in this research used multiple regression analysis with panel data. We found that tax avoidance is not associated with corporate risk. This result indicated that the company that conducts tax avoidance is not related to corporate risk. Furthermore, tax risk is not associated with corporate risk. Thus, tax risk could not capture corporate risk because corporate external factors may cause it.JEL Classification: C33, H26, G31DOI: https://doi.org/10.26905/jkdp.v22i4.2237